Analysis of Body Impact and the Role of Passive Safety Systems in Driver Injuries in Car-to-Car Collisions - Adinda Fadilah Hamdi; Lusi Susanti; Hilma Raimona Zadry; Alexie Harryandie Bronto Adi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Car-to-car collisions in Indonesia remain one of the leading causes of driver injuries. To date, vehicle safety evaluations have primarily focused on physical vehicle damage and environmental factors, while the characteristics of injuries sustained by drivers inside the cabin based on firsthand experience have rarely been analyzed. This study aims to analyze the relationship between injury severity, the location of the first point of impact, on the body, and the use of passive safety systems as a basis for developing recommendations for Advanced Driver Assistance Systems (ADAS) features. This study uses a quantitative approach based on an online questionnaire distributed to 100 car drivers in Indonesia who have been involved in car-to-car collisions. Data analysis was conducted descriptively using cross-tabulation and the Chi-Square test to examine relationships among injury severity, body impact location, and use of passive safety systems (seat belts and airbags). The results showed that 52% of respondents sustained minor injuries, 36% were uninjured, and 17% sustained severe injuries. The most common impact locations were the upper body (28%) and the head (23%). Statistical test results showed that the use of passive safety systems was not significantly associated with a reduction in injury severity (p = 0.078), but was significantly associated with the location of the impact (p = 0.001), which directly influenced injury severity (p = 0.026). Based on the analytical framework of these injury characteristics, the Forward Collision Warning (FCW), Automatic Emergency Braking (AEB), Intelligent Speed Assistance (ISA), and Proactive Passenger Protection System (PPS) features are recommended as top priorities for ADAS to reduce collision energy prior to a crash. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9 : Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production